Statistical analysis of the Economic Freedom Index - Sakharova, Evgenia (2014)
The Index of Economic Freedom is an indicator which defines and tries to measure the economic freedom of a country or a region. Economic freedom is a necessary condition for democratic development, prosperity and other positive outcomes. There are several indices of economic freedom which are published yearly from different organizations. The most famous are the Index of Economic Freedom created by the Heritage Foundation and the Wall Street Journal and Economic Freedom of the World published by the Canadian Fraser Institute. The indices consist of a number of components which are grouped in four or five broad categories. The aim of this thesis is to analyze the Economic Freedom of the World index. For this purpose two multivariate statistical methods will be used, namely factor analysis and hierarchical cluster analysis with the help of correlation analysis. The produced results will be compared with the existing indices.